PERLINDUNGAN TERHADAP ANAK DARI TINDAK KEKERASAN DITINJAU DARI UU NO 35 TAHUN 2014 MELALUI POLA ASUH KELUARGA DALAM PERSPEKTIF HUKUM ISLAM: PERLINDUNGAN TERHADAP ANAK DARI TINDAK KEKERASAN DITINJAU DARI UU NO 35 TAHUN 2014 MELALUI POLA ASUH KELUARGA DALAM PERSPEKTIF HUKUM ISLAM - Romdoni, Dede Hermin; Muslim, Pepep Puad; Habibi, Habibi (Usroh, 2023)
Forming children who have good behavior must start from the behavior of parents from an early age.Islam views that children's behavior in the future is a reflection of their parents and the education they taught them from an early age. The forms of violence that occur against children are physical, sexual and psychological. The diverse nature of Indonesian society, with the majority of the population being Muslim, means that law is a necessity that must be applied. The aim of this research is to determine the form of protection for children from acts of violence in terms of Law No. 35 of 2014 through family parenting patterns. This writing uses a descriptive analysis method using a normative juridical approach, because the author only studies and analyzes based on previously existing cases obtained from print media, newspapers, magazines, journals or online media, which are then analyzed using regulations. Laws and related legal theories. The results obtained from this research show that the government's efforts to protect acts of child violence through Law Number 35 of 2014 are very clear and detailed. Islamic law itself has explained that parents' obligations in caring for and educating children are mandatory and obligatory for parents, as stated by Allah SWT in the QS. Al-Tahrim verse 6. Education, religion and environment are the main factors in influencing parents' parenting patterns. Parental education really supports the parenting style that will be applied to children. Parents' religious beliefs cannot be separated from one of the factors influencing parenting patterns. Keywords: Child Violence; Child Protection; Parenting; Legal Protection